Application of General Cultural Competences in Supply Chain Management of the Business Success - Kotovchikhina Natalia Dmitrievna; Polozhentseva Irina Veniaminovna; Feoktistova Anna Borisovna; Yulia Galina Nikolaevna; Aralova Elena Viktorovna (International Journal of Supply Chain Management, 2018)
Abstract This paper presents an integrated view of the literature published on all aspects and facets of competence in supply chain management (SCM) revealing that the framework brings together aspects at the individual and organizational level of competence from SCM literature. The purpose of this paper is to explore and develop the general proposition that organizational cultural compatibility between strategic supply chain partners results in improved performance outcomes for each participant in the chain. A theoretical framework is proposed of the relationship of differing organizational cultural elements (practices, values, behaviors and norms) to supply chain performance.